PENGARUH KARAKTERISTIK PEMERINTAH DAERAH DAN OPINI AUDIT TERHADAP KINERJA PEMERINTAH PROVINSI DI INDONESIA - Mega Andani; Sarwani Sarwani; Novita Weningtyas Respati (UNIB Press, 2019)
This research aims to attest, examine and analyze the influence of local government characteristics and audit opinions on the performance of provincial governments in Indonesia. The characteristics of the local government are proxied by the size of the regional government, regional prosperity, capital expenditure. The performance of the provincial government uses a score indicator for Local Government Performance Evaluation (EKPPD). The population of this study amounted to 34 provincial governments in Indonesia from 2010-2016. The sampling method uses purposive sampling with a total sample of 30 provincial governments in Indonesia. Testing data using SPSS 23 program with multiple linear regression analysis. The results of this research indicate that the size of the local government and audit opinion have a positive effect on the performance of the provincial government, whereas regional prosperity and capital expenditure do not affect the performance of the provincial government.